KEMAMPUAN PENALARAN PROPORSIONAL MATEMATIS SISWA DENGAN GAYA BELAJAR FIELD INDEPENDENT - Azin Taufik (Department of Mathematics Education, Universitas Kuningan, 2021)
This study aims to describe the results of the analysis of students' mathematical proportional abilities in terms of independent field learning styles. This research was conducted at MTs Nurul Huda Beringin in September Odd Semester, Academic Year 2020/2021 with a total of 9 students of class VII A. The research subjects were selected by purposive sampling, consisting of 2 students with independent field cognitive style. The research method used is descriptive qualitative with a case research design. The data technique used the Group Embedded Figures Test, mathematical proportional reasoning ability tests, in-depth interviews and observations. Data analysis techniques were performed by data reduction, data presentation, and data retrieval. The technique of checking the validity of the data used the technique triangulation method. The results showed that: (1) There were 2 students who had a cognitive style in the field. (2) Students with field independent cognitive style, namely LH and DK subjects are at level 3 formal proportional reasoning, the second subject has been able to meet the indicators of finding values or quantities to compare, indicators find relationships between values or quantities and indicators use appropriate procedures in calculating comparisons.